TO LECTURE OR DISCUSS? TEACHING NON-NATIVE ENGLISH SPEAKERS STUDYING INTERNATIONAL RELATIONS AT WEBSTER UNIVERSITY, THAILAND - Rudolph, Rachael M. (Proceedings of the International Conference on Education, 2019)
Scholars have engaged the normative debates and contributed to the vast literature by focusing on the advantages and disadvantages of the didactic, student-centered and mixed-method approaches and their contribution to student achievement, motivation, performance and retention. Most of the studies conducted however, employ experimental and survey research methods thereby leaving qualitative case studies neglected. This is problematic because it is not possible to engage in a debate on how to implement teaching strategies and transform the classroom environment. This study qualitatively examines fifteen cases which have been taught by the author at Webster University’s Thailand Campus in the Department of History, Political Science and International Relations between 2013 and 2018. Case selection was based on the teaching approach, the level of the course (1000 to 4000 level), and the temporal range. The breadth of the cases covered and the emphasis on how the strategies were implemented open the door to an academic discussion on how to transform the pedagogical approach employed. A discussion on transformation of pedagogy is important in the 21st Century because of most primary, secondary and tertiary institutions are moving in the direction of adopting curricula and practices which are purely student-centered.